Impact of bismuth incorporation into (Ga, Mn)As thin films on their structural and magnetic properties. Issue 8 (5th June 2015) - Levchenko, K.; Andrearczyk, T.; Domagala, J. Z.; Wosinski, T.; Figielski, T.; Sadowski, J.; Seibt, M.
Abstract Structural and magnetic properties of thin films of the (Ga, Mn)(Bi, As) quaternary diluted magnetic semiconductor grown by the low‐temperature molecular‐beam epitaxy technique on GaAs substrates have been investigated. High‐resolution X‐ray diffraction has been applied to characterize the structural quality and misfit strain in the films. Ferromagnetic Curie temperature and magneto‐crystalline anisotropy of the films have been examined by using SQUID magnetometry and low‐temperature magneto‐transport measurements. Post‐growth annealing treatment of the films has been shown to reduce the strain in the films and to enhance their Curie temperature. Significant increase in the magnitude of magneto‐transport effects caused by incorporation of a small amount of Bi into the films is interpreted as a result of enhanced spin‐orbit coupling in the (Ga, Mn)(Bi, As) films. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)